Immunological aspects of host–pathogen crosstalk in the co-pathogenesis of diabetes and latent tuberculosis - Verma, Arpana; Kaur, Maninder; Luthra, Princy; Singh, Lakshyaveer; Aggarwal, Divya; Verma, Indu; Radotra, Bishan D.; Bhadada, Sanjay Kumar; Sharma, Sadhna (Frontiers in Cellular and Infection Microbiology, 2023)
Diabetes is a potent risk factor for the activation of latent tuberculosis and worsens the tuberculosis (TB) treatment outcome. The major reason for mortality and morbidity in diabetic patients is increased susceptibility to TB. Thus, the aim of the study is to understand the crosstalk between the M. tuberculosis and host upon latent tuberculosis infection and under hyperglycemic conditions/diabetes. An animal model was employed to study latent tuberculosis and diabetes. BCG immunization was done in mice before infection with M. tuberculosis and latency was confirmed by bacillary load, histopathological changes in lungs and gene expression of hspX, tgs1, tgs3 and tgs5. Diabetes was then induced by single high dose of streptozotocin (150mg/kg body weight). Host factors which play an important role in the containment of mycobacterial infection like various cytokines and MMPs were studied in vivo as well as in vitro. Murine model of latent TB was developed which was confirmed by CFU counts (<104 in lungs & spleen) together with the granuloma formation in lung tissue of latent TB group. Also, the gene expression of hspX, tgs1 and tgs5 was upregulated and after diabetes induction, blood glucose levels were >200mg/dl. In vitro study employing THP-1 macrophage model of latent and active tuberculosis under normal and high glucose conditions showed that dormant bacilli were better contained in presence of 5.5mM glucose concentration as compared to active bacilli. However, the killing and restriction efficiency of macrophages was decreased and CFU counts increased significantly with increase in glucose concentration. The decreased levels of MCP-1, decreased expression of mmp-9 and increased expression of mmp-1 in latent group at high glucose concentration could possibly explain the failure of granuloma formation at high glucose conditions.